Gemi - a Possible Tool for Identification of Disturbances in Coniferous Forests in Pernik Povince (Western Bulgaria) - Grigorov, Borislav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Global Environmental Monitoring Index (GEMI) represents a vegetation index that allows for making analysis. The index is not that sensitive to atmospheric effects. GEMI has been applied for the investigation of disruptions in the coniferous forests in Pernik Province, which is situated in the western parts of Bulgaria. The basic data comes from Landsat 8 and Corine Land Cover. The results of the study show that the index performs well in the distinguishment of broad-leaved vegetation from the coniferous one. At the same time the index doesn?t always provide satisfying results when it comes to deforestation. In conclusion GEMI provides good results, yet it?s use should be controlled and supported by other vegetation indices.
Keywords: remote sensing; forestry; deforestation; coniferous forests; teledetekcja; leśnictwo; wylesianie; las iglasty